2013
DOI: 10.1016/j.jand.2012.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics Associated with Consumption of Sports and Energy Drinks among US Adults: National Health Interview Survey, 2010

Abstract: Sales of sports and energy drinks have increased dramatically, but there is limited information on regular consumers of sports and energy drinks. Characteristics associated with sports and energy drink intake were examined among a sample representing the civilian noninstitutionalized US adult population. The 2010 National Health Interview Survey data for 25,492 adults (18 years of age or older; 48% males) were used. Nationwide, 31.3% of adults were sports and energy drink consumers during the past 7 days, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 31 publications
6
49
5
Order By: Relevance
“…This is consistent with previous research [21, 31] and would be expected given that energy drinks are heavily marketed towards young adults. Contrary to previous research, male gender was only significantly associated with ever having used an energy drink but not with past 30 day use (although males were more likely to have used within the past 30 days).…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous research [21, 31] and would be expected given that energy drinks are heavily marketed towards young adults. Contrary to previous research, male gender was only significantly associated with ever having used an energy drink but not with past 30 day use (although males were more likely to have used within the past 30 days).…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, the findings build on a growing number of studies that have raised concerns about the contribution of sugar-sweetened beverages to overall energy, added sugar, and sodium consumption among young adults (3, 16, 39) . The American Heart Association recommends that calories from added sugar be limited to approximately 418 kJ [100 kcal] per day for women and 628 kJ [150 kcal] per day for men (40) .…”
Section: Discussionmentioning
confidence: 84%
“…Yet, most of this literature failed to even discuss sugar content and largely focused on adverse effects due to the link between energy drinks and caffeine consumption, energy drinks and risk-taking behavior, in general, or sugary drinks excluding energy or sports drinks. However, in addition to the aforementioned points about energy drinks and the possible link between excess usage and obesity and among research focusing on the present topic of interest, a recent report by Park et al, 11 found that a high intake of regular soda, sweetened coffee or tea, fruit drinks, milk and alcohol were associated with a greater odds for drinking sports and energy drinks, which may not be acknowledged as sources of sugar. According to one report, 12 this may be because, while energy and sports drinks may have fewer calories and less sugar than regular soda, they enjoy health 'halos' that are not warranted due to an advertising focus on their cognitive benefits.…”
Section: Resultsmentioning
confidence: 88%
“…In addition, the many young people who continue to ingest regular soda, sweetened drinks and fruit drinks, may be more likely to also choose to drink sports and energy drinks on a weekly basis than those who don't, as well as suffering possible sleep loss, an obesity determinant. 11 Yet, despite the magnitude of the obesity problem among youth and adults and the possibility that energy and sports drinks may be compounding this, there are very few active solutions discussed or reported in the available literature about what should be done to combat this threat. Indeed, very few articles on this topic as a whole exist given that what has been published has raised highly significant concerns about the role of energy drinks in general and its sugar content in particular in a society where obesity is rampant and product consumption is encouraged through intense targeted marketing and has been increasing rapidly over the past 7-10years.…”
Section: Resultsmentioning
confidence: 99%